Decoding the role of cytochrome c in metabolism of human spermatozoa by Raman imaging - Abramczyk, Halina; Sobkiewicz, Bogna; Walczak-Jędrzejowska, Renata; Marchlewska, Katarzyna; Surmacki, Jakub (Frontiers in Cell and Developmental Biology, 2022)
The normal functioning of sperm cells requires cytochrome c in the redox balanced forms: reduced and oxidized. The oxidized form of cytochrome c is localized in the mito-chondrial intermembrane space and is a part of the electron transport chain. This ensures that electron shuttling between the complex III, cytochrome c, and complex IV can occur leading to controlled effective oxidative phosphorylation (respiration) and ATP production needed for most steps in spermatozoal maturation, motility, hyperactivation and fertiliza-tion. We studied the biochemical composition of specific organelles in sperm cells by Raman imaging. The structures of the head consisting of the nucleus and acrosome, the midpiece representing mitochondria, and the tail characterized by the sperm axoneme surrounded by outer dense fiber and covered by the membrane were measured. Metabolic biochemical analysis of mitochondria, head and tail of sperm cells, and seminal plasma by using Raman imaging combined with chemometric classification method of Cluster Analysis has been obtained. Our results show that cytochrome c, which is a key protein that is needed to maintain life (respiration) and cell death (apoptosis), is located in sperm mitochondria in the oxidized or reduced form of the heme group. This work demonstrated that an application of Raman micro-spectroscopy can be extended to monitoring the redox state of mitochondrial cytochrome c in sperm cells.